The Strategic Implementation Asset Management System Basis ISO 55000: A Case Study On Indonesian Railways Company - Hafizhuddin Ali (Profesional Muda Cendekia Publishing, 2021)
The purpose of this study is to investigate the implementation asset management system basis on ISO 55000. State-owned companies (SOE’s) in railways industry has a big asset across Sumatra, Java and Sulawesi Island. Railways SOE’s have a vision of becoming the best railroad service provider that focuses on customer service and meets stakeholder expectations. To relize the vision, Implementing ISO 55000 as asset management standards in corporation is important accordance to the vision in and mandatory of the Ministry of SOEs as stakeholders in managing strategic assets that are considered effective and efficient. In asset management, ISO 55000 Series is the international accepted standard which implemented in across industry. The purpose of this study is to determine the level of maturity in the existing asset management system against ISO 55000 and suggest improvements to the asset management system to achieve the certification of ISO 55000-based asset management. The method used is qualitative methods in case studies.The data from this study from deep interview by top managerial on Railways SOE’s. The analysis shown there is some clause whose level of maturity is doesn’t achieved competent level. Which raises a gap in the existing asset management system compared to ISO 55000 standards. One of these objects is the subject group Support, Context of Organization, and Performance Evaluation in ISO 55000 context and Risk & Review, Life Cycle Delivery, Asset Information, and Organization & People in the AM landscape developing level of maturity. As a result, an improvement in 2 aspects of asset management is recommended such as improvement on the basis of the asset management system and improvement on key performance indicators at Indonesia railways company.